A study on drug therapy issues in the department of medicine of a tertiary care teaching hospital-prospective observational study - J., Revathi; P., Venkatesh A.; C., Aswin; Mohanta, Guru Prasad; M., Senthilvelan (International Journal of Basic & Clinical Pharmacology, 2021)
Background: A drug therapy problem (DTP) is any undesirable event experienced by a patient that involves or is suspected to involve, drug therapy, and that interferes with achieving the desired goals of therapy. The improper use of drugs can lead to patient morbidity and even mortality. DTP s are the clinical territory of the pharmaceutical care practitioner and the resolution of identifying the DTPs help patients to achieve their goals of therapy. Identifying DTPs enables risk quantification and determination of the potential impact of prevention strategies. DTPs are associated with prolonged length of stay and increased economic burden and results in increased risk of death. Methods: A hospital based, prospective observational study was conducted at department of medicine in Rajah Muthiah medical college and hospital, 80 patients were enrolled in this study based on the inclusion-exclusion criteria. The DTPs were identified using the Cipolle’s method of classification of DTP. Results: The study has shown that 80 of the patients involved in the study had a total of 136 DTPs. An average of 1.7 DTPs were recorded per patient during the study. The most common DTP identified was unnecessary drug therapy accounting to 47%. The absence of valid medical indication was (30%) and (16%) were due to the duplication of therapy. The second most common DTP was unsafe drug for patients, accounting to 45% were due to patient non-compliance and drug interaction which was minor. Need for additional drug therapy was the third most identified accounting 13% were due to medical indication indicate the need of drug therapy. Conclusions: The foremost commonly observed DTP is unnecessary therapy and patient non-compliance to the drugs. The study suggests that DTPs are significantly occurring in hospital can cause the patient for comorbidity, prolonged hospitalization. The study suggests that clinical pharmacist and general practitioners can work together to spot and resolve the DTPs.